(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Objective (s): Aim of this study was to explore the efficacy of pretreatment with a combination of coenzyme Q10 (CoQ10) and dehydroepiandrosterone (DHEA) in comparison to that of DHEA alone before IVF-ICSI cycles in patients with diminished ovarian reserve. Methods: This retrospective case control study was conducted in Infertility Care and Research Center (ICRC) Ltd Dhaka, Bangladesh between January 2018 and December 2023. One hundred and forty (140) patients who had AMH level <1ng/ml and underwent ART after pretreatment by micronutrients were the candidates of this study. Among these patients fifty-six were treated with DHEA 75 mg /d and eighty-four patients were treated with combination of CoQ10 (600mg/d) and DHEA (75mg/d) for 90 days prior to IVF-ICSI cycles. Patients of combination of CoQ10 and DHEA group was considered as case (study) and only DHEA group as control. Main outcome measures were ovarian response to gonadotropin, amount and duration of gonadotropin needed to get optimum response, cycle cancellation, number of mature follicles ³18 mm, number of oocytes retrieved, fertilization and cleavage rate, number of good-quality embryos, number of embryo transferred, embryo freezing, clinical pregnancy and miscarriage rate. A p-value of < 0.05 was considered significant. Result: All patients’ baseline parameters were similar. There was no statistically significant difference of age, AMH, D3 FSH, E2, TSH and prolactin level. Ten patients (11.90%) of case and nine patients (16.07%) of control group did not develop any follicle in-spite of highest dose (450 IU/d) of gonadotropin and cycle was cancelled. Cancellation rate is more in control group though statistically was not significant (p=.480). The number of mature follicles ³18mm and oocytes retrieved was higher in the CoQ10+DHEA group compared to DHEA alone group (4.71±2.57 versus 3.7±2.5, p<0.005). A significantly lower amount of total gonadotropin dosages was needed in the Coq10+DHEA group compared to the DHEA group (3185±659 IUs versus 3642±1190 IUs, p=0.004). Fertilization rate, cleavage rate, and good quality embryo were significantly higher in women treated with Coq10 and DHEA than only DHEA group (3.73±2.19 versus 2.1±1.52, 3.65±2.17 versus 2.05±1.39, 2.35±1.45 versus 1.17±1.01 respectively, p<0.05). The rate of clinical pregnancy was also found significantly higher in CoQ10 and DHEA group than the only DHEA group (27.38% versus 8.9%, p=.0.007). A p value of <0.05 was considered significant. Conclusion: Pretreatment with CoQ10 and DHEA before ART increases ovarian responsiveness, number of oocytes, good-quality embryos, and pregnancy rates in patients with decreased ovarian reserve. Further large-scale study is required to establish the therapeutic effect of CoQ10 and DHEA. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 74-80